Pengaruh Penilaian Autentik terhadap Motivasi Belajar Siswa Kelas Dasar - Dita Maya Agustina; Mohamad Ayyub Mubtadik; Luluk Indarinul Mufidah; Wazirotus Sa'adah (IERA, Islamic Education and Research Academy, 2021)
Authentic assessment in the form of performance assessment based on previously learned knowledge is the focus of this research. The study aims to understand the Influence of Authentic Assessment on Learning Motivation of Grade III Students in Javanese Language Subject at MI Thoriqul Huda Juwet-Ngronggot. The motivation behind this title stems from the strong connection between assessment and motivation. A teacher's assessment should drive students' motivation to enhance their learning quality. This thesis includes a quantitative research design. Data collection involves observation, interviews, questionnaires, and documentation. The collected data is then analyzed, with the subsequent data analysis steps encompassing calculating authentic assessment results in Javanese language learning, scoring motivation questionnaires, and determining the influence of authentic assessment on student learning motivation using the Product Moment Correlation formula. The findings are as follows: (1) The application of authentic assessment in Grade III of MI Thoriqul Huda, specifically in Javanese language, is deemed excellent. This is substantiated by an average authentic assessment score of 84.6094. (2) Based on the questionnaire results about students' learning motivation in Javanese language, the score is remarkably high with an average score of 87.1875. (3) The calculation of the Product Moment Correlation formula reveals a significantly high correlation between authentic assessment and students' learning motivation in Javanese language. The correlation coefficient (rxy) is 0.75138, and the coefficient of determination is 57%, signifying that 57% of students' motivation in Javanese language learning at MI Thoriqul Huda Juwet-Ngronggot is influenced by authentic assessment.